Cognitive Control Network and Language Reorganization in Patients with Brain Tumors - Pasquini, Luca; Napolitano, Antonio; Spitoni, Leonardo; Schmid, Maurizio; Dellepiane, Francesco; Jenabi, Mehrnaz; Peck, Kyung; Holodny, Andrei (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: The interaction between language and other cognitive networks in patients harboring brain tumors is poorly understood. We studied the modification of the cognitive control network (CCN) induced by brain tumors and its participation in language reorganization. We hypothesized that patients with brain tumors and reorganized language would show a modification of the CCN compared with patients who remain left dominant.MATERIALS AND METHODS: Patients were selected with the criteria: newly diagnosed, pathologically-confirmed left-hemispheric tumor; single lesions; right-handedness; task-based and resting-state fMRI; no artifacts. Age-matched healthy controls (HC) were recruited from open-source databases. Language laterality was calculated by using task-based fMRI. We obtained the CCN through ad hoc independent component analysis on resting-state fMRI. Differences in CCN between patients and HC were characterized by cosine similarity (CS) and earth mover’s distance (EMD). Changes related to language reorganization and patients’ speech were assessed with the t test (P < .05). Results were corrected for multiple comparisons.RESULTS: One hundred forty-two right-handed patients (35 low-grade and 88 high-grade gliomas; 19 metastases) and 184 HC were included. Two independent components of the CCN were obtained. The t test confirmed significant effects of lateralization on the CCN (P = .004). Modification of CCN was associated with fewer speech deficits 1 week after surgery (P = .005).CONCLUSIONS: This study provides evidence that modifications of CCN occur in the setting of language reorganization. Patients exhibiting these modifications perform better at speech evaluation after surgery, suggesting a role of cognitive control in compensating for speech deficits when language reorganizes.AALautomated anatomic labelingADatypical dominantCCNcognitive control networkCScosine similarityEMDearth mover’s distanceFSLFMRIB Software LibraryG-ICAGroup ICAGIFTGroup ICA of the fMRI ToolboxGIG-ICAgroup-information guided ICAHChealthy controlHGGhigh-grade gliomaICindependent componentLDleft dominantLGGlow-grade gliomaLIlaterality indexMNIMontreal Neurological InstituteNVUneuro-vascular uncouplingRSNresting-state network